Childhood Sports Participation Is Associated With Health-Related Quality of Life in Young Men: A Retrospective Cross-Sectional Study - Appelqvist-Schmidlechner, Kaija; Kyröläinen, Heikki; Häkkinen, Arja; Vasankari, Tommi; Mäntysaari, Matti; Honkanen, Tuomas; Vaara, Jani P. (Frontiers in Sports and Active Living, 2021)
The aim of the study was to examine whether sports participation (SP), engagement in competitive sports (CS), and the type of sport undertaken at the age of 12 are associated with the physical and mental components of health-related quality of life (HRQoL) in young adulthood. The data were collected using questionnaires prior to a compulsory military refresher training course in Finland. The sample consisted of 784 men (mean age 26 years). HRQoL was measured with RAND 36 and childhood SP with a series of questions. Data were analyzed with logistic regression. Higher frequency of SP, participation in district-level CS; performing team, endurance, or extreme sports; and playing yard games in childhood were after adjustments all associated with better HRQoL in early adulthood. The association was mainly found with the mental component, and to a lesser extent with the physical component, of HRQoL. Team (OR 1.43, CI 1.00–2.06) and extreme sports (OR 1.77, CI 1.19–2.63) were associated with better mental HRQoL, while playing yard games (OR 0.62, CI 0.44–0.89) reduced the likelihood for having low physical HRQoL. SP in childhood—in the forms of team or individual sports, but also as informal physical activity, such as playing yard games—is associated with HRQoL in young adulthood.